2017
DOI: 10.1021/acs.jproteome.7b00449
|View full text |Cite
|
Sign up to set email alerts
|

New Insight of Common Regulatory Pathways in Human Trabecular Meshwork Cells in Response to Dexamethasone and Prednisolone Using an Integrated Quantitative Proteomics: SWATH and MRM-HR Mass Spectrometry

Abstract: The molecular pathophysiology of corticosteroid-induced ocular hypertension (CIH) is not well understood. To determine the biological mechanisms of CIH, this study investigated protein expression profiles of human trabecular meshwork (hTM) cells in response to dexamethasone and prednisolone treatment. Both discovery-based sequential windowed data independent acquisition of the total high-resolution mass spectra (SWATH-MS) and targeted based high resolution multiple reaction monitoring (MRM-HR) confirmation wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“… 3 reported no significant difference in the protein expression of fibronectin between human TM cells exposed to dexamethasone or those exposed to a control medium. In a similar experiment by Shan et al., 44 the protein expression of fibronectin was also not significantly changed in human TM cells exposed to dexamethasone when compared with TM cells exposed to a control medium. However, they reported that the protein expression of fibronectin was decreased in human TM cells exposed to prednisolone when compared with controls.…”
Section: Discussionmentioning
confidence: 66%
“… 3 reported no significant difference in the protein expression of fibronectin between human TM cells exposed to dexamethasone or those exposed to a control medium. In a similar experiment by Shan et al., 44 the protein expression of fibronectin was also not significantly changed in human TM cells exposed to dexamethasone when compared with TM cells exposed to a control medium. However, they reported that the protein expression of fibronectin was decreased in human TM cells exposed to prednisolone when compared with controls.…”
Section: Discussionmentioning
confidence: 66%
“…Moreover, it is becoming increasingly evident that several cell adhesive and certain actin-binding proteins, including actin, shuttle between the cytosolic and nuclear compartments to regulate transcriptional and chromatin remodeling activities ( Asp et al, 2002 ; Benmerah et al, 2003 ; Wang and Gilmore, 2003 ; Lundquist et al, 2014 ; Piccolo et al, 2014 ; Wang, 2014 ; Dupont, 2016 ; Chang et al, 2018 ; Klages-Mundt et al, 2018 ; Mahmood et al, 2021 ). Although several studies have examined the effects of glucocorticoids on the proteome and transcriptome profile of TM cells ( Lo et al, 2003 ; Nehme et al, 2009 ; Bollinger et al, 2012 ; Clark et al, 2013 ; Bermudez et al, 2017b ; Shan et al, 2017 ; Faralli et al, 2019 ), none of these have focused on characterizing the effects of glucocorticoids either on the cytoskeletome per se or on the nuclear fraction proteome of TM cells. To gain insights into glucocorticoid-induced cellar and molecular changes in the TM, especially changes involving actin cytoskeletal reorganization, cell adhesive interactions, and contractile characteristics, herein, we have utilized proteomics analysis to investigate the effects of Dex on the nuclear protein profile of human TM cells.…”
Section: Introductionmentioning
confidence: 99%
“…These models have facilitated understanding of the histological, proteomic, and genetic characteristics of SIG, but many unknowns remain. It is known that corticosteroids increase the production of myocilin, fibronectin, or other proteins of the extracellular matrix (Faralli et al., 2015 ; Shan et al., 2017 ), and inhibit the metalloproteinase that leads to excessive accumulation of extracellular matrix and hence the clogging of the trabecular meshwork. Corticosteroids also decrease phagocytic activity (Zeng et al., 2019 ) (the function of trabecular meshwork cells), which leads to an increase in retained material and rigidity in the trabecular meshwork (Raghunathan et al., 2015 ), altering the motility/regulation of the aqueous humor drainage pathways (Overby and Clark, 2015 ; Xin et al., 2017 ; Patel et al., 2019 , Patel et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%